Atovaquone attenuates experimental colitis by reducing neutrophil infiltration of colonic mucosa - Manzanares, Laura D.; David, Joseph; Ren, Xingsheng; Yalom, Lenore K.; Piccolo, Enzo B.; Dehghan, Yalda; David, Aidan J.; Hanauer, Stephen B.; Sumagin, Ronen (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC) is a chronic relapsing disease featuring aberrant accumulation of neutrophils in colonic mucosa and the luminal space. Although significant advances in UC therapy have been made with the development of novel biologics and small molecules targeting immune responses, success of most current therapies is still limited, with significant safety concerns. Thus, there is a need to develop additional safe and effective therapies for the treatment of UC. Antimalarial drugs have been safely used for many years to resolve tissue inflammation and the associated pathologies. Atovaquone is a recent FDA-approved antimalarial drug that has shown anti-viral and tumor-suppressive properties in vitro however, its role in mucosal inflammation has not been evaluated. Using pre-clinical murine DSS-induced colitis model combined with complementary in vivo peritonitis and ex vivo human neutrophil activation and chemotaxis assays we investigated functional and mechanistic impacts of atovaquone on disease resolution and neutrophil trafficking. We demonstrate that atovaquone promotes resolution of DSS-induced murine colitis by reducing neutrophil accumulation in the inflamed colonic mucosa. Mechanistically, we show that atovaquone suppressed induction of CD11b expression in neutrophils, reducing their polarization and migratory ability. Thus, our findings identify a new role of atovaquone in promoting resolution of mucosal inflammation, supporting the idea of potential repurposing of this FDA-approved drug as UC therapeutic.